Using magnetic nanoparticles/MIP-based electrochemical sensor for quantification of tetracycline in milk samples - Zeb, Shakeel [UNESP] (2021)
This paper reports the development of a biomimetic sensor and its application for the determination of tetracycline antibiotics. Tetracycline is an extremely vital antibiotic usually used for the treatment of people and livestock with bacterial disorder and respiratory issues. This antibiotic is widely used in poultry farms for the prevention of bacterial infection and the treatment of advanced bacterial growth. The sensor was constructed using magnetic nanoparticles (mag) and molecularly imprinted polymer (MIP). Based on the application of the co-precipitation approach, FeCl3·6H2O and FeCl2·4H2O salts were used to obtain core@shell magnetic nanoparticles. Prior to the synthesis of the selective MIP material, the density functional theory (DFT) was used to select the best functional monomer for the analyte investigated. After choosing the best monomer, the modified magnetic nanoparticles were used for the synthesis of the MIP in order to enhance the detection capability of the electrochemical sensor. The imprinted polymer was synthesized using optimized amounts of acrylic acid (functional monomer), ethylene–glycol-dimethacrylate (cross-linker), and 2,2 azobisisobutyronitrile (radical initiator). The control material – denoted by mag-NIP (magnetic non-molecularly imprinted polymer), which was used for comparison purposes, was synthesized based on the same procedure applied for the synthesis of the MIP but in the absence of the analyte (tetracycline). The analysis of surface morphology and the identification of the functional groups used in the synthesized magnetic materials were performed by fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), and high-resolution electron microscopy. The detection of tetracycline was performed under optimized conditions using square wave voltammetry, 15 mg of mag-MIP (on carbon paste), and 80 s of pre-concentration. Through the application of this analysis, well-defined peaks ranging from 0.5 to 1.0 V vs. Ag/AgCl (KClsat) were obtained. Analytical curves were constructed using the second peak at 0.83 V, and the following results were obtained: linear range of 5.0 × 10−7 to 4.0 × 10−5 mol L−1 (R2 of 0.9993), limit of detection (LOD) of 1.5 × 10−7 mol L−1 and repeatability of 2.82% (in terms of relative standard deviation) for n = 10. The results obtained from the analysis of selectivity demonstrated that the proposed electrochemical sensor is highly efficient for tetracycline determination. The sensor was successfully applied in commercial and raw milk samples for tetracycline detection, and recovery rates ranging from 93 − 103% were obtained. The results obtained show that the proposed electrochemical technique is suitable for application toward the determination of tetracycline.